Methodology of studying decompression zones in the waterproof stratum of potassium salts by ground and ground-underground gravimetry - Bychkov, S.G.; Michurin, A.V.; Prostolupov, G.V.; Simanov, A.A.; Khokhlova, V.V. (Perm Federal Research Centre Journal, 2019)
Research on the use of gravity data was carried out (supported by regional 2016-2018 contest RFBR) to predict negative engineering and geological phenomena caused by the process of potassium salt deposits exploitation. In the course of the project, techniques of high-precision ground-based, ground-underground gravimetric surveys and monitoring observations were developed, the adaptation of methods for processing gravimetric data of these surveys was performed methods for processing the gravimetric data of these surveys were adapted, computer-based algorithms for processing and interpreting observations were developed. Ways of interpreting dynamic anomalies, as well as ground and ground-underground gravimetric surveys based on the use of qualitative and quantitative methods for extracting geological information from gravimetric data, are proposed. Gravimetric monitoring in emergency areas of the mines of the Verkhnekamskoye potassium salt deposit has shown its high efficiency. It has been established that the dips of the earth surface and areas of increased subsidence caused by the flooding of the mines are clearly recorded in the gravitational field. By combining negative local gravity anomalies, which are interpreted as natural weakened zones, with negative dynamic anomalies associated with the decompression processes, hazardous geological processes can be successfully predicted.